Teaching Materials for Earth and Space Sciences Courses to Improve students Problem Solving - Ruslan; Yanti, Meili; M, Irmawati (Journal of Education Technology, 2024)
The current problem is that students' problem-solving abilities are still in the low category because students do not understand the problems given. Based on this, this study aims to develop teaching materials in the form of E-modules for Earth and Space Science courses. This research type uses the ADDIE learning design model (Analyze, Design, Develop, Implement, and Evaluate). The subjects of the study were two experts, namely media experts and material experts. The subjects of the trial were science education students, especially in semester III, totaling 34 students. Data collection methods used observation, interviews, and questionnaires. Data collection instruments used questionnaire sheets. The techniques used in analyzing data were qualitative and quantitative descriptive analysis. The results of the study showed that the validation results showed that the module was declared very valid in terms of content and media. The results of small-scale and group trials also showed that the developed E-module was practical. The results of the N-gain test showed a score of 77, which was categorized as high, indicating the effectiveness of the intervention. It is concluded that the E-module is validated and effective in developing teaching materials using the ADDIE model, with potential improvements identified for future literacy. This study implies that the E-module developed represents a significant step forward in preparing students with important problem-solving skills to prepare them for the challenges of the 21st century.